2019
DOI: 10.2306/scienceasia1513-1874.2019.45.452
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoids against various breast cancer subtypes: a molecular docking study

Abstract: Breast cancer is female most frequent diagnosed cancer and the leading cause of cancer death. The consumption of dietary flavonoids is reported to cause significant breast cancer risk reduction. In vitro studies often used aglycone flavonoids rather than its conjugated form that actually present in human body. Thus its mechanism against breast cancer has not been elucidated completely. The present study aimed to investigate the possible mechanism of dietary flavonoids against breast cancer by in silico study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Table 3 shows the comparison of identified compounds with previous studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ,…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the comparison of identified compounds with previous studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ,…”
Section: Resultsmentioning
confidence: 99%
“…Our in-silico investigations revealed that tannic acid showed the maximum binding energy against HER2 receptor and GCR compared to the standard (doxorubicin). Moreover, the literature cites the association of other important compounds like tangeretin, wogonin, quercetin, and other flavonoids that have shown lesser binding affinities with GCR and HER2 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, tannic acid (TA) has shown maximum binding energy against Her2 receptor rather than the standard drug doxorubicin. As far as the previous studies were concerned compounds like Tangeretin, wogonin, quercetin, and other avonoids have shown less binding energy to the GC and Her2 receptor with respect to present studies [24,25].…”
Section: Discussionmentioning
confidence: 50%